The Impact of ESG Factors on Firm Value with Profitability as a Moderator in the Healthcare Industry - Annisa Rulitasari; Andam Dewi Syarif (International Journal Labs, 2026)
The healthcare industry faces increasing pressure to enhance firm value while complying with Environmental, Social, and Governance (ESG) standards. Environmental costs related to medical waste management, social accountability, and governance structures are critical issues for hospitals and laboratories listed on the Indonesia Stock Exchange. However, empirical findings regarding the effect of ESG factors on firm value remain inconsistent, particularly concerning the moderating role of profitability. This study aims to examine the effect of Environmental Sustainability Disclosure, Social Sustainability Disclosure, and Managerial Ownership on Firm Value proxied by Tobin's Q, with profitability (ROA) as a moderating variable. The research employs a quantitative approach using panel data from seven healthcare companies during 2019–2024. Data were analyzed using Moderated Regression Analysis (MRA) with EViews software. The results indicate that Social Sustainability Disclosure and profitability significantly influence firm value, whereas Environmental Sustainability Disclosure and Managerial Ownership do not have a direct significant effect. Profitability strengthens the relationship between Environmental Sustainability Disclosure and firm value but fails to moderate Social Sustainability Disclosure and negatively moderates Managerial Ownership. In conclusion, profitability plays a strategic moderating role, and social disclosures are more strongly valued by investors compared to environmental and governance factors in the Indonesian healthcare sector.